Flexibilização curricular: a proposta do ensino médio inovador e a profissionalização do ensinar - Pinto, Marcelo Barbosa (2016)
The Innovative High School Program (ProEMI), created by the government by means of the Ministry of Education, presents a proposal which might modify the current educational scenario. Instituted in 2009, it aims to support and develop transforming curricular proposals in Brazilian schools which have regular high school classes. By means of the pursuit of overcoming the inequality, and the improvement of the educational opportunities, the Program indicates the necessity of universalizing the access and permanence of the teenagers between 15 and 17 years old in this modality. In order to achieve this, a significant learning offer and the recognition of the dialogue with several cultures are elements that take priority in the referred program. By ensuring the access, the curricular flexibility proposed in the ProEMI has the intention of attending to these desires, preparing the adolescent both for their enrollment at higher education and for the job market. The ProEMI aims to achieve the curricular integration as a possibility of change. Thus, as the focus of this dissertation, we analyzed the major concepts that the ProEMI proposes for High School, in which we attempted to answer whether the curricular flexibility proposed provides possibilities for some changes in this learning modality, in such a way as to understand how the changes will be introduced, as well as which alterations will be provided for the teacher s professional profile and for their teaching. Therefore, it was intended to apprehend the limits and possibilities of this Program to the formation of a new High School. It was also an interest to discuss aspects related to the process of educational innovation in geography teaching, in order to observe how the Program implicates in geography teaching, and what changes are made in the teachers profile.